2011
DOI: 10.1007/s10661-011-2073-z
|View full text |Cite
|
Sign up to set email alerts
|

Occurrences of six steroid estrogens from different effluents in Beijing, China

Abstract: Concentration levels of six natural and anthropogenic origin steroid estrogens, namely, diethylstilbestrol (DES), estrone (E1), estradiol (E2), estriol (E3), ethinylestradiol (EE2), and estradiol-17-valerate (Ev), from different effluents in Beijing were assessed. Sampling sites include two wastewater treatment plants (WWTPs), a chemical plant, a hospital, a pharmaceutical factory, a hennery, and a fish pool. In general, concentrations of estrogens in the effluents varied from no detection (nd) to 11.1 ng/l, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 46 publications
3
31
3
1
Order By: Relevance
“…A similar result has been reported in a municipal sewage treatment plant in Wuhan, China (Jin et al 2008). The relatively high influent concentration of EE2 in our studied WWTP may be due to correlative industry discharge (Cui et al 2006;Zhou et al 2011) or/and different consumption rates of contraceptive pills compared to other regions. For steroid estrogens E2, E3, and EE2, the seasonal influent concentration was in the order of spring>autumn>summer>winter.…”
Section: Seasonal Concentration Variation Of Steroid Estrogens In Wwtsupporting
confidence: 88%
See 2 more Smart Citations
“…A similar result has been reported in a municipal sewage treatment plant in Wuhan, China (Jin et al 2008). The relatively high influent concentration of EE2 in our studied WWTP may be due to correlative industry discharge (Cui et al 2006;Zhou et al 2011) or/and different consumption rates of contraceptive pills compared to other regions. For steroid estrogens E2, E3, and EE2, the seasonal influent concentration was in the order of spring>autumn>summer>winter.…”
Section: Seasonal Concentration Variation Of Steroid Estrogens In Wwtsupporting
confidence: 88%
“…2, for influent, E1 and E3 were the main contributors and accounted for >60%. Because only 1-2% of administered EE2 is transformed to E1, E2, or E3 (Ranney 1977) and, compared with natural E2 excretion, the amount of E2 in pharmaceutical usage is <5% (Christensen 1998), the higher relative abundance of natural estrogens should be due to human excretions (Zhou et al 2011). A study in Japan has also concluded that human estrogens are the major estrogenic compounds in sewage and effluent (Matsui et al 2000).…”
Section: Levels Of Steroid Estrogens In Wwtp Influent and Effluentmentioning
confidence: 99%
See 1 more Smart Citation
“…DEHP is a plasticizer that is commonly used in polyvinyl chloride products to improve their flexibility [6]. DES is a synthetic estrogen that is routinely used to prevent spontaneous abortion [15]. Nonylphenol (NP) is widely used as a surfactant in laundry and cleaning practices and is a steady metabolite of nonylphenol ethoxylates in a natural environment [7].…”
Section: Potential Chemicals In Hwwmentioning
confidence: 99%
“…Broséus et al achieved more than 80% removal rate for caffeine, pharmaceuticals, and EDCs with the use of ozone (2 mg·min/L) to treat wastewater [27]. However, HWW is rarely involved in previous research on EDC removal via ozone because most of DeS nc Cancer, immune system, and reproductive effects [15,22] nP nc Cancer, development, and reproductive effects [23] a Average concentration; nd: below detectable limit; nc: uncertain.…”
Section: Efficiency Of Edc Removal Via Ozonementioning
confidence: 99%